2023
DOI: 10.1038/s41598-023-42934-0
|View full text |Cite
|
Sign up to set email alerts
|

Validating virtual administration of neuropsychological testing in Parkinson disease: a pilot study

Julia Gallagher,
Eugenia Mamikonyan,
Sharon X. Xie
et al.

Abstract: COVID-19 has highlighted the need for remote cognitive testing, but the reliability and validity of virtual cognitive testing in Parkinson disease (PD) is unknown. Therefore, we assessed PD participants enrolled in an observational, cognition-focused study with an extensive cognitive battery completed both in-person and via video conference close in time. Data for 35 PD participants with normal cognition to mild dementia were analyzed. Only one test (semantic verbal fluency) demonstrated a difference in score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Though these studies did not include any performance-based tasks, which are likely more susceptible to the effects of poor task engagement than self-report questionnaires, the results nonetheless suggest that fully remote and unsupervised interactions with participants are feasible for Parkinson's disease research. Second, with respect to reliability, one study compared the test-retest reliability of standard in-person testing to supervised virtual testing in Parkinson's patients, where patients were at home and supervised by a rater on a video call [10]. The results of this study showed that though test-retest reliability between the in-person and virtual administration varied across tasks, many of the tasks achieved at least moderate reliability, which is a level of reliability comparable to that of standard in-person paper-based cognitive testing in Parkinson's patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Though these studies did not include any performance-based tasks, which are likely more susceptible to the effects of poor task engagement than self-report questionnaires, the results nonetheless suggest that fully remote and unsupervised interactions with participants are feasible for Parkinson's disease research. Second, with respect to reliability, one study compared the test-retest reliability of standard in-person testing to supervised virtual testing in Parkinson's patients, where patients were at home and supervised by a rater on a video call [10]. The results of this study showed that though test-retest reliability between the in-person and virtual administration varied across tasks, many of the tasks achieved at least moderate reliability, which is a level of reliability comparable to that of standard in-person paper-based cognitive testing in Parkinson's patients [11].…”
Section: Introductionmentioning
confidence: 99%